Waqf-based private forest management model: case study in Bogor Regency, Indonesia - Restiyani, Destika; Hardjanto; Hasanah, Neneng (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
As in Bogor Waqf Forest, a waqf-based private forest management pattern was developed in Indonesia. Waqf currently functions not only for constructing mosques, cemeteries, and orphanages, but also for environmental preservation, known as green waqf. This study analyzed the mechanism of waqf forest development and waqf forest management practices in Bogor Regency. The method used Exploratory research was conducted using primary and secondary data. The informants were selected using purposive sampling. The data were analyzed qualitatively. The results showed that Bogor Waqf Forest Foundation collected donations in the form of zakat, infaq, and waqf (ziswaf) for the development of the Bogor Waqf Forest. In addition, the Bogor Waqf Forest Foundation collaborates with BAZNAS and the Ministry of Religious Affairs to manage Bogor Waqf Forest productively by empowering local communities by forming groups such as the Berkah Bersama Group, Giat Bersama Group, Citra Berdikari Group, KUB Asri Berseri, and Kelompok Tanggap Bencana (KATANA). Bogor Waqf Forest Management applies agroforestry forest management practices, such as agrosilvofishery, agrosilvopasture, apiculture, and agrisilviculture, which are non-timber product-oriented, namely NTFPs and environmental services.